Association between suicide idea and anxiety sensitivity in obsessive-compulsive disorder: A controlled study - Ay, Rukiye; Kılınçel, Oğuzhan (Journal of Surgery and Medicine, 2020)
Aim: Obsessive-compulsive disorder (OCD) is associated with suicide risk, but controversy remains about the frequency and burden of suicidality in OCD. This study aimed to identify the relationship between anxiety sensitivity and suicidal idea in patients with OCD. Methods: This controlled study included 36 OCD patients and 36 healthy controls. All individuals were evaluated with Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Anxiety Sensitivity Index-3 (ASI-3) and Suicide Probability Scale (SPS). Demographic data were obtained from each patient. Results: Seventy-two individuals with a mean age of 31.89 (9.69) years were included in this study. No significant differences were found between the groups with regards to individual and family histories of suicide attempt and the presence of other chronic diseases (P>0.05 for each). The patients had significantly higher BDI, BAI and ASI-3 scores than the controls (P>0.05 for each). There were significant correlations between BDI, BAI, ASI-3 and SPS desperation, suicide ideation scores, hostility scores and total scores (P<0.05 for each). Conclusion: The present study revealed that depression and anxiety status are important for suicide risk in OCD patients. Therefore, it is recommended to always evaluate the risk of suicide in these patients.